Flexibility of adjustment to shocks: Economic growth and volatility of middle-income countries before and after the Global Financial Crisis of 2008 - Joshua Aizenman; Yothin Jinjarak; Gemma Estrada; Shu Tian (Asian Development Bank (ADB), 2017)
The pronounced and persistent impact of the global financial crisis of 2008 motivates our empirical analysis of the role of institutions and macroeconomic fundamentals on countries' adjustment to shocks. Our empirical analysis shows that the associations of growth level, growth volatility, shocks, institutions, and macroeconomic fundamentals have changed in important ways after the crisis. Gross domestic product growth across countries has become more dependent on external factors, including global growth, global oil prices, and global financial volatility. After accounting for the effects global shocks, we find that several factors facilitate adjustment to shocks in middle-income countries. Educational attainment, share of manufacturing output in gross domestic product, and exchange rate stability increase the level of economic growth, while exchange rate flexibility, education attainment, and lack of political polarization reduce the volatility of economic growth. Countries cope with shocks better in the short to medium term by using appropriate policy tools and having good long-term fundamentals.
Keywords: C38; E02; F43; 330; growth; institutions; middle income; shocks; volatility; Wirtschaftswachstum; Konjunktur; Wirtschaftliche Anpassung; Institutionelle Infrastruktur; Schwellenländer; Finanzkrise; Schock; Konjunkturzusammenhang; Welt